Step-by-step explanation:
- 3x+5y=7b equation 1
- 2x+4y=1
2x=-4y+1
- x=(-4y+1)/2
- x=(-4y+1)/2 in equation 1
3×(-4y+1)/2+5y=7b
(-12y+3)/2+5y=7b
(-12y+3+10y)/2=7b
(-12y+3)/2=7b
-12y+3=14b
-12y=14b-3
- y=3-14b/12
- y=3-14b/12 in x=(-4y+1)/2
x=(-4×{3-14b/12}+1)/2
x=(-3+14b)/3+1/2
x=14b/3×1/2
Answer:
A:48 B:45
Step-by-step explanation:
Answer:
broke
Step-by-step explanation:
----$$$$$$$
Answer:
y = -4
Step-by-step explanation:
-2x + 5y = 8
Let x=-14
-2(-14) +5y = 8
28 +5y = 8
Subtract 28 from each side
28-28 +5y = 8-28
5y = -20
Divide by 5
5y/5 = -20/5
y = -4
Answer:
3√(22) + 7
Step-by-step explanation:
The way this is worded can be interpreted two different ways so just to cover the bases, I'll do both. I'm confident they are asking for way 1 though because it wants you to simplify the expression, not evaluate. Way 2 gives you a solution rather than an exact equation.
<u>Number 1</u>
√(6) x √(33) + 7
= √(6 x 33) + 7
= √(198) + 7
= √(9 x 22) + 7
= 3√(22) + 7
<u>Number 2</u>
√(6) x √(33 + 7)
= √(6) x √(40)
= √(6) x (4√(10))
= 4√(60)
= 8√(15)